Semiconductors: 25th Anniversary Article: Materials for High‐Performance Biodegradable Semiconductor Devices (Adv. Mater. 13/2014). (April 2014) - Hwang, Suk‐Won; Park, Gayoung; Cheng, Huanyu; Song, Jun‐Kyul; Kang, Seung‐Kyun; Yin, Lan; Kim, Jae‐Hwan; Omenetto, Fiorenzo G.; Huang, Yonggang; Lee, Kyung‐Mi; Rogers, John A.
<x xml:space="preserve">Abstract</x> The cover image shows a partially dissolved piece of silicon‐based electronics built entirely using biologically and environmentally benign materials. This type of technology, sometimes referred to as transient electronics, offers potential applications in bioresorbable medical devices, ecofriendly electronics, environmental sensors, secure hardware systems, for example, and is reviewed by J. A. Rogers, K. M. Lee, and co‐workers on page 1992. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>